2016
DOI: 10.1242/jeb.130815
|View full text |Cite
|
Sign up to set email alerts
|

Sequential steps of macroautophagy and chaperone-mediated autophagy are involved in the irreversible process of posterior silk gland histolysis during metamorphosis ofBombyx mori

Abstract: To elucidate the degradation process of the posterior silk gland during metamorphosis of the silkworm Bombyx mori, tissues collected on the 6th day after entering the 5th instar (V6), prior to spinning (PS), during spinning (SP) and after cocoon formation (CO) were used to analyze macroautophagy, chaperone-mediated autophagy (CMA) and the adenosine triphosphate (ATP)-dependent ubiquitin proteasome. Immediately after entering metamorphosis stage PS, the levels of ATP and phosphorylated p70S6 kinase protein decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Traditionally, autophagy is orchestrated by the group of ATG proteins, which precisely control the autophagic process ( 11 , 19 ). The process kickstarts the formation of the pre-initiation complex, followed by generation of the phagophore, autophagosome, and autolysosome, leading to cargo degradation (Figure 1 B) ( 11 , 19 , 20 ). Mammalian target of rapamycin complex 1 inhibition leads to the induction of autophagy and assembles ULK1/2, ATG13, and FIP200 to form the pre-initiation complex at the phagophore (Figure 1 B).…”
Section: Autophagy As a Cell Survival Mechanismmentioning
confidence: 99%
“…Traditionally, autophagy is orchestrated by the group of ATG proteins, which precisely control the autophagic process ( 11 , 19 ). The process kickstarts the formation of the pre-initiation complex, followed by generation of the phagophore, autophagosome, and autolysosome, leading to cargo degradation (Figure 1 B) ( 11 , 19 , 20 ). Mammalian target of rapamycin complex 1 inhibition leads to the induction of autophagy and assembles ULK1/2, ATG13, and FIP200 to form the pre-initiation complex at the phagophore (Figure 1 B).…”
Section: Autophagy As a Cell Survival Mechanismmentioning
confidence: 99%
“…Recent studies have shown that autophagy and apoptosis are induced prior to metamorphosis in the Drosophila fat body (Lindmo et al , ), silkworm posterior silk gland (Shiba et al , ), silkworm midgut (Franzetti et al , ) and fat body (Tian et al , ). We found that BmVps4 was also up‐regulated before metamorphosis, indicating a similarly early induction of the MVB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiological functions of MVB proteins in metamorphosis are rarely reported. During metamorphosis, larval tissues and organs are completely degraded or transformed into pupal or adult forms, and some adult‐specific tissues and organs are de novo formed from imaginal discs (Romanelli et al , , ; Shiba et al , ). The degradation process requires highly active autophagy and apoptosis, and the formation of tissues and organs requires active cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Sequentially, the process is initiated by the formation of the pre-initiation complex, developed by the elongation and completion of the autophagosome, and finished with the generation of autolysosome to degrade cargoes. 13,14 In general, the functional components involved in the process include the UNC-51-like kinase (ULK) complex, ATG5-ATG12-ATG16L1 conjugation systems, the Beclin 1 class III phosphatidylinositol 3-kinase (PI3K) complex, and the microtubule-associated protein 1 light chain 3 (LC3) conjugation systems (Figure 1). 15 The pre-initiation complex consists of ULK1, FIP200 (FAK family kinase-interacting protein of 200 kDa), ATG13, and ATG101.…”
Section: The Molecul Ar Machinery and Reg Ul Ation Of Autophagymentioning
confidence: 99%